Clinical outcomes and treatment necessity in patients with toxin-negative Clostridioides difficile stool samples - Dae Hyeon Cho; Si-Ho Kim; Cheon Hoo Jeon; Hyoung Tae Kim; Kyoung-Jin Park; Junyoung Kim; Jiyeong Kwak; Byung Soo Kwan; Sungmin Kong; Jung Won Lee; Kwang Min Kim; Yu Mi Wi (Annals of Clinical Microbiology and Antimicrobials, 2024)
Abstract Purpose The clinical significance of negative toxin enzyme immunoassays (EIA) for Clostridioides difficile infections (CDIs) is unclear. Our study aimed to investigate the significance of toxin EIA-negative in the diagnosis and prognosis of CDI. Methods All stool specimens submitted for C. difficile toxin EIA testing were cultured to isolate C. difficile. In-house PCR for tcdA, tcdB, cdtA, and cdtB genes were performed using C. difficile isolates. Stool specimens were tested with C. difficile toxins A and B using EIA kit (RIDASCREEN Clostridium difficile toxin A/B, R-Biopharm AG, Darmstadt, Germany). Characteristics and subsequent CDI episodes of toxin EIA-negative and -positive patients were compared. Results Among 190 C. difficile PCR-positive patients, 83 (43.7%) were toxin EIA-negative. Multivariate analysis revealed independent associations toxin EIA-negative results and shorter hospital stays (OR = 0.98, 95% CI 0.96–0.99, p = 0.013) and less high-risk antibiotic exposure in the preceding month (OR = 0.38, 95% CI 0.16–0.94, p = 0.035). Toxin EIA-negative patients displayed a significantly lower white blood cell count rate (11.0 vs. 35.4%, p < 0.001). Among the 54 patients who were toxin EIA-negative and did not receive CDI treatment, three (5.6%) were diagnosed with CDI after 7–21 days without complication. Conclusion Our study demonstrates that toxin EIA-negative patients had milder laboratory findings and no complications, despite not receiving treatment. Prolonged hospitalisation and exposure to high-risk antibiotics could potentially serve as markers for the development of toxin EIA-positive CDI.